Knowledge, barriers and facilitators of exercise in dialysis patients: a qualitative study of patients, staff and nephrologists. Issue 1 (December 2016) - Jhamb, Manisha; McNulty, Mary; Ingalsbe, Gerald; Childers, Julie; Schell, Jane; Conroy, Molly; Forman, Daniel; Hergenroeder, Andrea; Dew, Mary
Abstract Background Despite growing evidence on benefits of increased physical activity in hemodialysis (HD) patients and safety of intra-dialytic exercise, it is not part of standard clinical care, resulting in a missed opportunity to improve clinical outcomes in these patients. To develop a successful exercise program for HD patients, it is critical to understand patients', staff and nephrologists' knowledge, barriers, motivators and preferences for patient exercise. Methods In-depth interviews were conducted with a purposive sample of HD patients, staff and nephrologists from 4 dialysis units. The data collection, analysis and interpretation followed Criteria for Reporting Qualitative Research guidelines. Using grounded theory, emergent themes were identified, discussed and organized into major themes and subthemes. Results We interviewed 16 in-center HD patients (mean age 60 years, 50% females, 63% blacks), 14 dialysis staff members (6 nurses, 3 technicians, 2 dietitians, 1 social worker, 2 unit administrators) and 6 nephrologists (50% females, 50% in private practice). Although majority of the participants viewed exercise as beneficial for overall health, most patients failed to recognize potential mental health benefits. Most commonly reported barriers to exercise were dialysis-related fatigue, comorbid health conditions and lack of motivation. Specifically for intra-dialytic exercise, participants expressed concern over safety and type of exercise, impact on staff workload and resistance to changing dialysis routine. One of the most important motivators identified was support from friends, family and health care providers. Specific recommendations for an intra-dialytic exercise program included building a culture of exercise in the dialysis unit, and providing an individualized engaging program that incorporates education and incentives for exercising. Conclusion Patients, staff and nephrologists perceive a number of barriers to exercise, some of which may be modifiable. Participants desired an individualized intra-dialytic exercise program which incorporates education and motivation, and they provided a number of recommendations that should be considered when implementing such a program.